...Más, mejor - Suka Fiszman, Nicolás (2010)
Comentarios sobre la trayectoria del estudio paulista.
Keywords: GRUPO SP; PUNTONI, ÁLVARO; SODRÉ, JOÃO; DAVIES, JONATHAN; ARQUITECTURA; ESTUDIOS DE ARQUITECTURA; BRASIL; REGIÓN SUDESTE; SAO PAULO; SAN PABLO